Safeguarding Historical Heritage Amid Environmental and Human-Induced Threats: A Spatial Risk Management Study of the Muaro Jambi Temple Compound - Hendra Gunawan; Saldi Yulistian; Charisma Cahaya (JAMBURA GEO EDUCATION JOURNAL, 2026)
The Muaro Jambi Temple Compound, recognized as one of the most extensive cultural heritage sites in Southeast Asia, faces numerous threats stemming from both natural phenomena and anthropogenic activities. This study aims to systematically identify and assess potential risks, determine their severity and probability, and propose effective risk management strategies to support the site's long-term conservation. Utilizing the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) framework, the research adopts a mixed-methods approach, combining qualitative and quantitative analyses supported by Geographic Information Systems (GIS) and SPSS-based statistical tools. The findings highlight five major risks: coal dust pollution, climate-induced flooding, artifact theft, vandalism, and inadequate conservation funding. Among these, coal dust pollution is identified as the most critical threat due to its high frequency and substantial impact on both the structural integrity of the temple complex and surrounding community health. The study proposes mitigation strategies including strengthened industrial regulations, improved drainage infrastructure, and active community engagement in heritage preservation efforts. This research underscores the necessity of an integrated and collaborative risk management approach to safeguard cultural heritage assets like the Muaro Jambi Temple Compound in the face of escalating environmental and socio-economic pressures